Effect of magnetic islands on the impurity flows in NCSX geometry - Shishkin, A.; Mynick, H. (Вопросы атомной науки и техники, 2005)
A new physics idea to protect a plasma from impurity ions with the use of magnetic islands can be examined on the new National Compact Stellarator Experiment device (NCSX), which is under construction at Princeton Plasma Physics Laboratory, USA. On the basis of the MHD approach the impurity ions flows are studied in the configuration with the parameters of NCSX with the magnetic islands m / n=5/3 and m / n=6/3 , which can be excited with the trim coils in NCSX. It is shown that solving the flow trajectory equations dr × uα =0 can lead us to the conclusion that ion flow trajectories are concentrated in the region of the magnetic islands. Нову фізичну ідею захисту плазми від проникнення іонів домішки за допомогою магнітних островів можна перевірити в експериментах на новому пристрої National Compact Stellarator Experiment (NCSX), який споруджується в Princeton Plasma Physics Laboratory, USA. На основі МГД наближення потоки іонів домішки вивчаються для конфігурації з параметрами NCSX з магнітними островами з «хвильовими» числами m / n=5/3 and m / n=6/3, які можна збудити спеціальними токовыми катушками (trim coils) у NCSX. Рішення рівнянь траєкторій потоків dr × uα =0 доводить, що потоки іонів можуть концентруватися в межах магнітних островів. Новая физическая идея - защитить плазму от проникновения примесных ионов c использованием магнитных островов - может быть проверена в экспериментах на новой установке National Compact Stellarator Experiment (NCSX), строящейся в Princeton Plasma Physics Laboratory, USA. На основе МГД приближения потоки ионов примеси изучаются для конфигурации с параметрами NCSX с магнитными островами с «волновыми» числами m / n=5/3 и m / n=6/3, которые могут быть возбуждены специальными токовыми катушками (trim coils) в NCSX. В результате решения уравнений траекторий потоков dr × uα =0 показано, что потоки ионов могут концентрироваться в области магнитных островов.